Alternative management of soilborne pathogens of melon crop and detection of multiple viruses from fruit crops - Borges, Darlan Ferreira (Universidade Federal Rural do Semi-Árido, 2020)
The cultivation of melon (Cucumis melo L.) is extremely important for the Brazilian economy. The country is the thirteenth largest melon producer in the world and the third in Latin America. However, even with high melon production, the damages triggered by soilborne pathogens cause losses in production and yield and risk the abandonment of melon cultivated areas. Thus, in order to improve quality and productivity, it is necessary to develop new techniques that can help in the management of soilborne pathogens, which are the main drive of losses in melon cultivation. Many control techniques are already being used to manage such pathogens, such as chemical, biological control, and the use of natural products; however, little is known about the use of green manure associated with polyethylene mulch to that end. Therefore, the objective of this research was to evaluate the effect of incorporating plant materials (Crotalaria juncea L. and Pennisetum glaucum L.) and commercial products (Compost- Aid® + Soil-Set®) to efficiently control pathogens transmitted via soil in melon production. In addition, we evaluated the responses of the soil microbiota (total fungi, total bacteria, sporulating bacteria, and total actinomycetes) to the above treatments. Two identical greenhouse experiments were conducted in a completely randomized design with seven treatments and seven replications. In conclusion, with part of this work, we were able to generate practical and theoretical information for producers to facilitate the management of the main soilborne pathogens that cause damage to the melon root system, optimizing techniques (mulch and green manure) that are already being used by the melon producers. During the second part my research, which was carried out in the United States of America (USA), different viruses in fruit trees were studied. In this study, our main goal was to determine the incidence and prevalence of grapevine viruses in the New England region vineyards. These viruses can cause losses of $ 25,000 to $ 40,000 per hectare and even replacement of entire vineyard in cases of high incidence of the viruses. Many of the grapevine viruses investigated in our study had previously been found in the state of New York (NY). Based on the proximity of NY to the New England region and the fact that grape growers from this region buy much of their plant material from NY nurseries, it was expected that the viruses already described in NY would be detected in New England. To address this hypothesis, we partially sequenced specific genes from each virus species identified in our study and phylogenetically compared those sequences with virus sequences from different origins in the world and in the U.S. The second part of the research carried out in the USA was the writing of a review on fig mosaic disease. The USA is the eighth largest fig producer in the world, around 28,300 tons is produced each year, with the state of California being the largest producer. Typical fig mosaic disease symptoms such as chlorotic and yellowish spots, discoloration, deformation, and mosaic patterns on leaves and fruits have been observed in fig trees for almost a century, but the etiological agents associated with fig mosaic disease have only been investigated in the last decade. Twelve viruses - fig leaf mottle-associated virus 1 (FLMaV-1), fig leaf mottleassociated virus 2 (FLMaV-2), fig leaf mottle-associated virus 3 (FLMaV-3), Arkansas fig closterovirus-1 (AFCV-1), Arkansas fig closterovirus-2 (AFCV-2), fig mosaic emaravirus virus (FMV), fig latent virus 1 (FLV-1), fig mild mottle-associated virus (FMMaV), fig cryptic virus (FCV), fig fleck-associated virus (FFKaV), and fig badnavirus 1 (FBV-1) - and three viroids - apple dimple fruit viroid (ADFVd), citrus exocortis viroid (CEVd), ands hop stunt viroid (HSVd) - are associated with the disease. In this review, we proposed the standardization of the name of each virus, the conduction of geographic studies of the disease, and the development of isolation protocols to study these viruses and viroids in vivo. Furthermore, we suggested the conduction proper disease resistance tests, development of diagnoses assays and phylogenetic studies
Keywords: Cucumis melo L.; Manejo de doenças; Microbiota; Viroses da videira; Mosaico da figueira; Cucumis melo L.; Disease management; Microbiota; Grapevine viruses; Fig mosaic disease; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA